MAPK/ERK Signaling Pathway Analysis in Primary Osteoblasts from Patients with Nonsyndromic Sagittal Craniosynostosis. (January 2014) - Kim, Sun-Don; Yagnik, Garima; Cunningham, Michael L.; Kim, Jinoh; Boyadjiev, Simeon A.
Objective: The MAPK/ERK signaling pathway has been implicated in several craniosynostosis syndromes and represents a plausible target for therapeutic management of craniosynostosis. The causes of sagittal nonsyndromic craniosynostosis (sNSC) have not been well understood and the role that MAPK/ERK signaling cascade plays in this condition warrants an investigation. We hypothesized that MAPK-signaling is misregulated in calvarial osteoblasts derived from patients with sNSC. Methods: In order to analyze if the MAPK/ERK pathway is perturbed in sNSC, we established primary calvarial osteoblast cell lines from patients undergoing surgery for correction of this congenital anomaly. Appropriate negative and positive control cell lines were used for comparison, and we examined the levels of phosphorylated ERK by immunoblotting. Results: Primary osteoblasts from patients with sNSC showed no difference in ERK1/2 phosphorylation with or without FGF2 stimulation as compared with control osteoblasts. Conclusion: Under the described test conditions, we did not observe convincing evidence that MAPK/ERK signaling contributes to the development of sNSC.